(3bUjOI GdoHSJi GdfhfjIs - (3Ydj Hf eMeO Hf GdMSjf Hf jhSa Hf eMeO Hf YHO GdYRjR GdHSJj, CHh GdaJM,J (B400 (3g` s
(3ChdgG (B:s
(3RjGOI GdeQA aj OfjGg fbUGf hQHMI ZjQ eMV GdNjQ NSQGf s
(3BNQgG (B:s
(3hCHYK Edjg SdGekG RGcjkG YWQkG hGdBd hGdUMH dG jafjg CReGf s
(3JJab eY GdfSNI GdChdi aj ChdgG hJNJda eYgG aj BNQgGs
(3fSNI KGfjIs
(3hJRjO Yf GdfSNI GdChdi KeGfjI CHjGJs
(3hHgG fXGe GdJYbjHIs
(3hQO CjVkG JMJ Qbe (B2182 s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs